2008
DOI: 10.1007/s00531-008-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

The final rifting evolution at deep magma-poor passive margins from Iberia-Newfoundland: a new point of view

Abstract: In classical rift models, deformation is either uniformly distributed leading to symmetric fault bounded basins overlying stretched ductile lower crust (e.g. pure shear McKenzie model) or asymmetric and controlled by large scale detachment faulting (simple shear Wernicke model). In both cases rifting is considered as a mono-phase process and breakup is instantaneous resulting in the juxtaposition of continental and oceanic crust. The contact between these two types of crusts is often assumed to be sharp and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
297
2
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(327 citation statements)
references
References 47 publications
10
297
2
5
Order By: Relevance
“…9). Such a temporary subsidence delay has also been widely reported from either magma poor passive continental margin like the Iberia-Newfoundland (Kusznir and Karner 2007;Péron-Pinvidic and Manatschal 2009), or magma rich passive margins, such as the North-eastern Atlantic margin (Clift 1997) and Pakistan volcanic margin (Claves et al 2008). In this way, the continental margins subsides less than might be expected from the observed crustal thinning and resulting isostatic response.…”
Section: Cenozoic Tectonics As a Major Controlling Factormentioning
confidence: 67%
“…9). Such a temporary subsidence delay has also been widely reported from either magma poor passive continental margin like the Iberia-Newfoundland (Kusznir and Karner 2007;Péron-Pinvidic and Manatschal 2009), or magma rich passive margins, such as the North-eastern Atlantic margin (Clift 1997) and Pakistan volcanic margin (Claves et al 2008). In this way, the continental margins subsides less than might be expected from the observed crustal thinning and resulting isostatic response.…”
Section: Cenozoic Tectonics As a Major Controlling Factormentioning
confidence: 67%
“…The ultramafic rocks in such settings mainly represent inherited sub-continental lithospheric mantle exhumed onto the seafloor and the structurally interleaved sedimentary rocks represent its syn-to post-rift cover (Manatschal 2004;Péron-Pinvidic and Manatschal 2009). The complex polyphase structural history and the relatively high pressures recorded in the mafic schist (Willner et al 2012) are another feature typical of OCT zones, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In general, syn-rift magmatism is subdued and is represented by mafic intrusions of MORB-like composition; volcanic rocks commonly form a minor component of the mafic magmatism (but see Bernoulli et al 2003). These mafic intrusions record the onset of magmatic accretion within the OCT zone during distributed (delocalized) extension-related deformation, which commonly continues for a significant length of time (Jagoutz et al 2007;Péron-Pinvidic and Manatschal 2009), until the onset of true seafloor spreading and the formation of oceanic crust.…”
Section: Characteristics Of Hyperextended Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of modern high-quality geophysical data, deep sea drilling and comparative studies of analogue areas onshore (e.g. Manatschal 2004;Péron-Pinvidic and Manatschal 2009) has shown that the OCT of magma-poor passive margins is a zone of hyperextension characterized by extreme thinning of parts of the continental crust, resulting in exhumation of the lowermost crust and/or serpentinized continental mantle onto the seafloor (e.g. Iberian margin, Tucholke et al 2007;Sibuet and Tucholke 2013).…”
Section: Introductionmentioning
confidence: 99%